THE SGIE ABBREVIATION JOKE IN THE 2024 PRESIDENTIAL AND VICE PRESIDENTIAL DEBATE: A NETNOGRAPHIC STUDY OF TIKTOK POSTS WITH THE HASHTAG #SGIE - Mardhiyyah, Mardhiyyah; Arswendi, Riki (Universitas Mercu Buana, 2025)
The General Election (Pemilu) is a democratic event held every five years by the Indonesian people to elect the President and Vice President. The next election will take place on February 14, 2024. There are three pairs of presidential and vice-presidential candidates who will compete: Pair Number 1, Anies Rasyid Baswedan and Muhaimin Iskandar; Pair Number 2, Prabowo Subianto and Gibran Rakabuming Raka; and Pair Number 3, Ganjar Pranowo and Mahfud MD. As in previous elections, the General Election Commission (KPU) will organize five debate sessions, comprising three for presidential candidates and two for vice-presidential candidates. So far, two debates have been held—one for each candidate type. An intriguing moment occurred during the vice-presidential debate on December 22, 2023, when one candidate asked another about the abbreviation